This study aims to determine the PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PASIEN: STUDI PADA PASIEN RAWAT INAP - herlina lusiana; Firdaus - (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2020)
Abstract, This research aims to determine the effect of service quality on patient satisfaction. The independent variables in this research were Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5). Whereas Patient Satisfaction (Y) is used as the dependent variable. The research was conducted at Banjarmasin Islamic Hospital. The population used is inpatients who come from January 2019 s.d. October 2019 numbered 7,770 people. The sample was used as many as 99 respondents using the slovin formula with an estimated error of 10%. The sampling technique is simple random sampling technique. This research is an explanatory research with a quantitative approach. The data analysis method uses multiple linear regression and t test. The results showed that patient satisfaction consisting of Tangibles (X1), Reliability (X2), Responsiveness (X3), Assurance (X4) and Empathy (X5) variables affected the Satisfaction of Inpatients at Banjarmasin Islamic Hospital. Responsiveness variables have a more dominant influence on patient satisfaction.